1988
DOI: 10.1002/ana.410230507
|View full text |Cite
|
Sign up to set email alerts
|

Lesch‐nyhan syndrome: A study of motor behavior and cerebrospinal fluid neurotransmitters

Abstract: We studied 5 boys, 2 to 10 years old, with marked or complete deficiency of hypoxanthine-guanine phosphoribosyltransferase and Lesch-Nyhan syndrome with varying degrees of mental retardation, dysarthria, chorea, dystonia, spasticity, and ataxia. Four patients had marked reduction of homovanillic acid in the cerebrospinal fluid (CSF) and all showed low CSF 3-methoxy-4-hydroxy phenylethylene glycol, indicating reduced dopamine and norepinephrine turnover. Three patients showed high CSF 5-hydroxyindoleacetic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 19 publications
7
49
0
Order By: Relevance
“…The abnormally low DHPG levels may thus represent an adaptive mechanism to spare NE levels, possibly mediated by reduced MAO activity. This finding is consistent with the report of low CSF MHPG in 5 LN boys (Jankovic et al 1988), and low to normal plasma levels of NE in 14 LN subjects compared to controls (Lake and Ziegler 1977). Of interest, central noradrenergic function was reported to be normal in postmortem biochemical analyses of NE concentration (Lloyd et al 1981), and in a genetic mouse model of LN (Jinnah et al 1994).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The abnormally low DHPG levels may thus represent an adaptive mechanism to spare NE levels, possibly mediated by reduced MAO activity. This finding is consistent with the report of low CSF MHPG in 5 LN boys (Jankovic et al 1988), and low to normal plasma levels of NE in 14 LN subjects compared to controls (Lake and Ziegler 1977). Of interest, central noradrenergic function was reported to be normal in postmortem biochemical analyses of NE concentration (Lloyd et al 1981), and in a genetic mouse model of LN (Jinnah et al 1994).…”
Section: Discussionsupporting
confidence: 89%
“…Notwithstanding, EPI concentrations have not been assessed in any of the published biochemical studies of LN disease (Rockson 1974;Lake and Ziegler 1977;Silverstein et al 1985;Jankovic et al 1988). In contrast, NE levels have been reported to be normal or reduced at baseline, and irresponsive to postural changes (Lake and Ziegler 1977;Rockson 1974), or to exposure to cold (Rockson 1974).…”
Section: Discussionmentioning
confidence: 99%
“…In some of these disorders, dopamine metabolite disturbances have already been reported, such as the presence of low CSF HVA values in phenylketonuria 21,22 and Lesch-Nyhan disease. 23 In addition, these kinds of diseases that involve the brain in a diffuse manner are commonly associated with structural brain abnormalities. In our study we have observed that cortical atrophy disclosed by brain MRI tends to be related to low 5-HIAA concentrations.…”
Section: (3) Neurogenetic Conditionsmentioning
confidence: 99%
“…Despite the absence of neurobehavioral deficits in these mice, several studies have demonstrated neurochemical abnormalities that are strikingly similar to those observed in Lesch-Nyhan disease. In particular, these animals have significant deficits in brain dopamine levels (Finger et al, 1988;Dunnett and Sirinathsinghji, 1989;Williamson et al, 199 1;Jinnah et al, 1993) similar to those that occur in Lesch-Nyhan patients (Lloyd et al, 198 1;Silverstein et al, 1985;Jankovic et al, 1988). The occurrence of this defect in the HPRTmice provides a unique tool for studying the relationship between HPRT deficiency and brain dopamine systems.…”
mentioning
confidence: 98%